Globalization and the urban poor in China - Yin Zhang; Guanghua Wan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper examines the distributional impact of globalization on the poor in urban China. Employing the kernel density estimation technique, we recovered from irregularly grouped household survey data the income distribution for 29 Chinese provinces for 1988-2001. Panels of the income shares of the poorest 20, 10 and 5 per cent of the urban residents were then compiled. In a fixed-effect model, two of the central conclusions of Dollar and Kraay (2002)—that `the incomes of the poor rise equi-proportionately with average income' and that trade openness has little distributional effect on poverty—were revisited. Our results lend little support to either of the Dollar-Kraay conclusions, but instead indicate that average income growth is associated with worsening income distribution while globalization in general, and trade openness in particular, raises the income shares of the poor. It is also found that openness to trade and openness to FDI have differential distributional effects. The beneficial effect of trade was not restricted to the coastal provinces only, but also weakened significantly after 1992. These findings are robust to allow for nonlinearity in the effect of globalization and to control for the influence of several other variables. – globalization ; poverty ; China
Keywords: O15; O53; 330; Städtische Armut; Einkommensverteilung; Globalisierung; China